Evaluation of alleles at OsAGPS2, OsAGPL2, and OsSUT1 related to grain filling in rice in a common genetic background. Issue 2 (25th January 2021) - Kato, Tsuneo; Morita, Ryutaro; Ootsuka, Shinjiro; Wakabayashi, Yu; Aoki, Naohiro; Horibata, Akira
Abstract: Poor grain filling, characterized by incidence of partially filled grain, is one of the major problems to be improved for maximizing the yield potential in rice ( Oryza sativa L.) cultivars with numerous spikelets in a panicle (extra‐heavy panicle type [EHPT]). This study evaluated the grain‐filling‐related alleles at APS2 and APL2, the loci for the small and large subunits of ADP‐glucose pyrophosphorylase (AGPase), respectively, and at SUT1, sucrose transporter, for their effects and interactions on grain filling and associated traits of EHPT cultivars. Two sets of derived lines were developed. Each of these lines was one of the eight possible homozygotes of alleles derived from rice cultivars Akenohoshi and Milyang 23 at the three loci in nearly common genetic backgrounds. They were examined for grain‐filling traits in two different years. Results showed that APL2‐2, and SUT1‐2 in part, derived from Milyang 23 showing relatively good grain filling, significantly improved grain filling compared with APL2‐1 and SUT1‐1 from Akenohoshi showing poor filling. This improvement in grain filling may result from increased AGPase activity and expression of APL2 and SUT1 proteins, by means of APL2‐2 and SUT1‐2 . However, the variations in AGPase activity, protein expression, and the degree of grain filling were not associated with the gene expression of the three loci, implying post‐transcriptional regulation. These results strongly suggested that APL2‐2 and SUT1‐2 are associated with good grain filling. Core Ideas: Rice extra‐heavy panicle types did not always realize higher yield due to low grain filling. Alleles at three rice loci related to grain filling were evaluated in a common genetic background. APL2‐2 and SUT1‐2 should be used in the breeding of rice extra‐heavy panicle types.